Assessment of polymorphic metabolite data in bioavailability/bioequivalence studies – considerations and challenges - Srinivas, Nuggehally R (Asian Journal of Pharmaceutics (AJP), 2014)
Bioavailability (BA)/ bioequivalence (BE) studies are the cornerstone for the approval of generic drugs. While BA/BE assessment involving the pharmacokinetic data of the parent compound has been routinely performed, the introduction of the assessment of metabolite(s) data, alone or in addition to parent compound, has also emerged. In this context, the assessment of BA/BE of metabolite(s) may pose additional complexities and challenges, if the metabolic pathway is under the influence of a polymorphic enzyme. This communication provides brief perspectives on the challenges and study design considerations for the assessment of polymorphic metabolite in BA/BE studies.